2005
DOI: 10.1158/1078-0432.ccr-05-1436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epidermal Growth Factor Receptor Expression Level on Survival in Patients with Epithelial Ovarian Cancer

Abstract: Background: Several lines of laboratory evidence support the epidermal growth factor receptor (EGFR) as an adverse prognostic indicator in ovarian cancers. However, different methods of immunohistochemical assessment have yielded conflicting results. Here, we sought to determine the prognostic value of EGFR in ovarian cancer using a novel method of compartmentalized in situ protein analysis. Methods: A tissue array composed of 150 advanced-stage ovarian cancers uniformly treated, with surgical debulking follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
106
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 25 publications
7
106
2
2
Order By: Relevance
“…We did not observe any association between EGFR and HER-2/ neu immunostaining and disease outcome, confirming results of a previous study also from our institution (Van Der Zee et al, 1995). Previous studies on the relationship between EGFR or HER-2/neu overexpression and clinicopathological characteristics, response to chemotherapy and survival have shown conflicting results Elie et al, 2004;Nielsen et al, 2004;Psyrri et al, 2005). One of the most important reasons for these inconclusive data is the considerable methodological variability among studies (Hall et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…We did not observe any association between EGFR and HER-2/ neu immunostaining and disease outcome, confirming results of a previous study also from our institution (Van Der Zee et al, 1995). Previous studies on the relationship between EGFR or HER-2/neu overexpression and clinicopathological characteristics, response to chemotherapy and survival have shown conflicting results Elie et al, 2004;Nielsen et al, 2004;Psyrri et al, 2005). One of the most important reasons for these inconclusive data is the considerable methodological variability among studies (Hall et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Cetuximab, an anti-EGFR monoclonal antibody (mAb), targets cancer cells overexpressing EGFR. EGFR is an important molecule for targeting cancer cells that displays elevated expression in up to 70% of EOCs (33) and in many other carcinomas (34) (SI Text, Note S4). Although EGFR targeting is the focus here, immunoconjugate synthesis, imaging, and taPIT are all generalizable such that a variety of targeting molecules for other tumor antigens may be applied (SI Text, Note S2).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the studies evaluating the prognostic role of EGFR expression are also conflicting. Some studies suggested EGFR positivity as a negative prognostic factor (Skirnisdottir et al, 2001;Psyrri et al, 2005;Lassus et al, 2006;Noske et al, 2011) and demonstrated an association with poorer survival rates, while others reported no relationship between disease outcome and EGFR expression (Nielsen et al, 2004;de Graeff et al, 2008). Variations in IHC procedures, antibodies, and patient selection may provide some explanation for the differing results from these studies.…”
Section: Discussionmentioning
confidence: 99%